Solvothermal Synthesis of Calcium Hydroxyapatite via Hydrolysis of Alpha-Tricalcium Phosphate in the Presence of Different Organic Additives - Karalkeviciene, Rasa; Raudonyte-Svirbutaviciene, Eva; Zarkov, Aleksej; Yang, Jen-Chang; Popov, Anatoli I.; Kareiva, Aivaras (MDPI, 2023)
In this study, the effects of sodium lauryl sulfate and various amino acids (DL-aspartic acid, dodecanedioic acid, and suberic acid) on the formation of calcium-deficient hydroxyapatite via hydrolysis of α-tricalcium phosphate (α-TCP) were investigated; moreover, a combined effect of these additives and ethylene glycol as a synthesis medium was also estimated. The hydrolysis reaction was performed in solutions containing different concentrations of additives in aqueous and mixed aqueous–organic media under solvothermal conditions. It was demonstrated that the nature and the concentration of organic additives influence the phase purity and morphology of the final product. Higher concentrations of sodium lauryl sulfate and dodecanedioic acid induced the formation of impurities in addition to hydroxyapatite, while aspartic and suberic acid did not affect the phase purity. The morphology of the samples varied from plate- to rod-like depending on the concentrations of specific organic additive. --//-- This is an open access article Karalkeviciene R, Raudonyte-Svirbutaviciene E, Zarkov A, Yang J-C, Popov AI, Kareiva A. Solvothermal Synthesis of Calcium Hydroxyapatite via Hydrolysis of Alpha-Tricalcium Phosphate in the Presence of Different Organic Additives. Crystals. 2023; 13(2):265. https://doi.org/10.3390/cryst13020265 published under the CC BY 4.0 licence.
This research was funded by the grant WHITCERAM (No. S-LJB-22-1) from the Research Council of Lithuania. Institute of Solid State Physics, University of Latvia as the Center of Excellence has received funding from the European Union’s Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART².
Keywords: Research Subject Categories::NATURAL SCIENCES; calcium hydroxyapatite; α-tricalcium phosphate; amino acids; organic additives; solvothermal synthesis